DIGITALISASI DESA SEBAGAI UPAYA PERCEPATAN PELAYANAN PUBLIK DALAM MEWUJUDKAN GOOD GOVERNANCE - Kusroh Lailiyah (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2022)
ABSTRACT This study aims to determine the implementation of village digitization as an effort to accelerate public services in realizing good governance. The method used in this research is qualitative method. The approach that the researcher uses is a literature study. The results of this study indicate that the direction and policies of village development until 2030 refer to Presidential Regulation (Perpres) Number 59 of 2019 concerning the Sustainable Development Goals. There are three big things that are targeted, namely First, National Economic Recovery (PEN) according to village authority which relies on the revitalization of BUMDes and BUMDes. This is very possible because so far BUMDes will become a legal entity after the work creation law is passed. Second, the provision of village electricity and third, productive economic development managed by BUMDes and BUMDesma. Then related to the National Priority Program in accordance with the village authority, namely village data collection, resource mapping and the development of information and communication technology (ICT). There are four digital village design models, namely digitization for database preparation for villages based on Big Data, digitization for superior village development, digitization to accelerate village government services, digitization to increase financial transparency and village development activities. Keyword: Village Digitization, Good Governance, Public Services